2010
DOI: 10.1111/j.1524-4725.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Excision and PET-CT in the Initial Stage of Malignant Melanoma

Abstract: SLNE is much more sensitive than PET-CT in discovering small lymph node metastases. We consider PET-CT unsuitable for the evaluation of early regional lymphatic tumor dissemination in this patient population and recommend that it be limited to malignant melanomas of American Joint Committee on Cancer stages III and IV. We therefore recommend the routine use of SLNE for tumor staging and stratification for adjuvant therapy of patients with stage I and II malignant melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 30 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Recently, Klode et al [21] sought to clarify the role of SLNB in the evaluation of the initial stages of 61 patients with primary melanoma (AJCC stages I and II; Breslow thickness >1 mm) by comparing it directly with FDG-PET/CT evaluation. Metastatic SLNs were found in 14 patients (23%); 17 metastatic lymph nodes were detected overall, only one of which was identified preoperatively using FDG-PET/CT.…”
Section: Comparison Between Fdg-pet and Slnb For Regional Lymph Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Klode et al [21] sought to clarify the role of SLNB in the evaluation of the initial stages of 61 patients with primary melanoma (AJCC stages I and II; Breslow thickness >1 mm) by comparing it directly with FDG-PET/CT evaluation. Metastatic SLNs were found in 14 patients (23%); 17 metastatic lymph nodes were detected overall, only one of which was identified preoperatively using FDG-PET/CT.…”
Section: Comparison Between Fdg-pet and Slnb For Regional Lymph Nomentioning
confidence: 99%
“…The results of this study showed that initial-stage FDG-PET/CT in patients with AJCC stage I or II melanoma does not offer any advantage over SLNB with respect to the detection of local and regional metastases, because lymph nodal micrometastases cannot reliably be detected. SLNB, on the other hand, is a more sensitive procedure to diagnose lymph nodal metastases of melanoma and continues to be the criterion standard for the classification and stratification for adjuvant therapy of patients with AJCC stage I or II melanoma [21]. …”
Section: Comparison Between Fdg-pet and Slnb For Regional Lymph Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in breast cancer patients, the sensitivity, specificity, PPV, NPV and accuracy of FDG PET/CT was 58, 92, 82, 77 and 79%, indicating that FDG PET/CT cannot replace invasive approaches for axillary staging but may extend the indication for SLNB [117]. Low sensitivity of PET/CT also has been reported in patients with primary malignant melanoma [118]. …”
Section: Pet Imaging Of Lymphatic Systemmentioning
confidence: 99%
“…A study by Klode et al [43] directly compared SLNE and 18 F-FDG PET/CT in the evaluation of early-stage melanoma metastasis by analyzing data from 61 patients with primary malignant melanoma with a Breslow index > 1.0 mm. SLN involvement was found in 14 patients (23%).…”
Section: Comparison Of 18 F-fdg Pet (Pet/ct) and Slnb For Detecting Rmentioning
confidence: 99%